2021
DOI: 10.1007/s40544-021-0507-3
|View full text |Cite
|
Sign up to set email alerts
|

Capillary electroosmosis properties of water lubricants with different electroosmotic additives under a steel-on-steel sliding interface

Abstract: The process of lubricant penetration into frictional interfaces has not been fully established, hence compromising their tribological performance. In this study, the penetration characteristics of deionized water (DI water) containing an electroosmotic suppressant (cetyltrimethylammonium bromide (CTAB)) and an electroosmotic promoter (sodium lauriminodipropionate (SLI)), were investigated using steel-on-steel friction pairs. The results indicated that the lubricant with electroosmotic promoter reduced the coef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 53 publications
0
6
0
Order By: Relevance
“…The different morphology of the wear tracks and ball surface indicates that the wear mechanism under the two sliding motions is different. According to Feng et al, a hard iron oxide layer is formed on the worn surface when sliding under deionized water [38], which is also proved by the Raman mapping results in figure 8. The hard iron oxide layer (Fe 2 O 3 ) can protect the disk from being worn, thus decreasing the wear rate of the disk under USM.…”
Section: Friction and Wear Of Aisi E52100 Steel Lubricated By Pao 40 ...mentioning
confidence: 68%
See 1 more Smart Citation
“…The different morphology of the wear tracks and ball surface indicates that the wear mechanism under the two sliding motions is different. According to Feng et al, a hard iron oxide layer is formed on the worn surface when sliding under deionized water [38], which is also proved by the Raman mapping results in figure 8. The hard iron oxide layer (Fe 2 O 3 ) can protect the disk from being worn, thus decreasing the wear rate of the disk under USM.…”
Section: Friction and Wear Of Aisi E52100 Steel Lubricated By Pao 40 ...mentioning
confidence: 68%
“…In terms of USM, the worn area of the PTFE substrate is relatively smooth, which is accompanied by the production of a large amount of parallel slight ploughings. The parallel slight plowings are attributed to the discrete transfer layer [38]. Moreover, the discrete transfer layer could also decrease the COF and wear rate under USM.…”
Section: Friction and Wear Of Dlc Coating And Ptfe Bulk Materialsmentioning
confidence: 91%
“…To ensure the considerable electroosmotic performance of the compound cutting fluid and taking into account the amount of general EP additive, the concentration of MOA-3P was set at 0.75 wt% in preparing the water-based cutting fluid (named WCF). To further improve the electroosmotic performance, electroosmotic regulators are often added to the cutting fluid [16,27]. The electroosmotic regulation characteristic of cutting fluid with more complex components is still unclear, which limits the application of the electroosmosis effect in tribology.…”
Section: Electroosmotic Characteristics Of Compound Cutting Fluidsmentioning
confidence: 99%
“…Zhao et al [19] and Brown et al [20] also indicated that the absolute value of the zeta potential decreased with increased ionic strength, which was due to the compression of the EDL by high ionic strength to reduce the charge density in the EDL. Additionally, ionic surfactants adsorbed to charged surfaces by electrostatic or van der Waals forces could significantly affect the zeta potential and have been commonly used to regulate EOF [21][22][23][24][25][26][27]. At present, there is still little research on zeta potentials at friction material/cutting-fluid interfaces, and the influences of cutting-fluid components on zeta potential and EOF need to be further revealed.…”
Section: Introductionmentioning
confidence: 99%
“…Guo et al [25] achieved low-friction coefficients (0.01-0.03) by employing self-mated ceramics, self-mated cemented carbide, and cemented carbide/ceramic under water lubrication. Feng et al [26] found that the deionized water (DI water) containing an electroosmotic promoter (sodium lauriminodipropionate (SLI)) reduced the coefficient of friction and wear scar diameter, whereas, that with an electroosmotic suppressant (cetyltrimethylammonium bromide (CTAB)), exhibited an opposite behavior. Ji et al [27] reported that glyceryl monostearate (GMS)-filled microcapsules largely improved the tribological properties of drilling mud.…”
Section: Additives In Water-based Lubricationmentioning
confidence: 99%